Evaluation of Gastric Disease with Capsule Endoscopy - Seung-Joo Nam; Hyun Seok Lee; Yun Jeong Lim (Korean Society of Gastrointestinal Endoscopy, 2018)
The clinical indication for capsule endoscopy has expanded from small bowel evaluation to include esophagus or colon evaluation. Nevertheless, the role of capsule endoscopy in evaluation of the stomach is very limited because of the large volume and surface. However, efforts to develop an active locomotion system for capsule manipulation in detailed gastric evaluation are ongoing, because the technique is non-invasive, convenient, and safe, and requires no sedation. Studies have successfully reported gastric evaluation using a magnetic-controlled capsule endoscopy system. Advances in technology suggest that capsule endoscopy will have a major role not only in the evaluation of gastric disorders but also in the pathologic diagnosis, intervention, and treatment of any gastrointestinal tract disorder.